The Driving Force for the Acylation of β‐Lactam Antibiotics by L, D‐Transpeptidase 2: Quantum Mechanics/Molecular Mechanics (QM/MM) Study. Issue 9 (10th April 2019) - Ibeji, Collins U.; Lawal, Monsurat M.; Tolufashe, Gideon F.; Govender, Thavendran; Naicker, Tricia; Maguire, Glenn E. M.; Lamichhane, Gyanu; Kruger, Hendrik G.; Honarparvar, Bahareh
Abstract: β ‐lactam antibiotics, which are used to treat infectious diseases, are currently the most widely used class of antibiotics. This study focused on the chemical reactivity of five‐ and six‐membered ring systems attached to the β ‐lactam ring. The ring strain energy (RSE), force constant (FC) of amide (C−N), acylation transition states and second‐order perturbation stabilization energies of 13 basic structural units of β ‐lactam derivatives were computed using the M06‐2X and G3/B3LYP multistep method. In the ring strain calculations, an isodesmic reaction scheme was used to obtain the total energies. RSE is relatively greater in the five‐(1a–2c) compared to the six‐membered ring systems except for 4b, which gives a RSE that is comparable to five‐membered ring lactams. These variations were also observed in the calculated inter‐atomic amide bond distances (C−N), which is why the six‐membered ring lactams C−N bond are more rigid than those with five‐membered ring lactams. The calculated ΔG # values from the acylation reaction of the lactams (involving the S−H group of the cysteine active residue from L, D transpeptidase 2) revealed a faster rate of C−N cleavage in the five‐membered ring lactams especially in the 1–2 derivatives (17.58 kcal mol −1 ). This observation is also reflected in the calculated amide bond force constant (1.26 mDyn/A) indicating a weaker bond strength, suggesting that electronic factors (electron delocalization) play more of a role on reactivity of the β ‐lactam ring, than ring strain. Abstract : β ‐lactam antibiotics, which are used to treat infectious diseases, are currently the most effective class of antibiotics. This study focuses on the chemical reactivity of five‐ and six‐membered ring systems attached to the β ‐lactam ring.